European Works Councils Experiences; Dosẃiadczenia europejskich rad zakładowych - Katarzyna Skorupinśka (Comparative Economic Research. Central and Eastern Europe, 2011)
In September, 2011 there was 15th anniversary of the implementation of the first EU directive creating European Works Councils (EWCs). This is also the year when the new version of the directive was put in force, i.e. Directive 2009/38/EC. EWCs are a form of indirect employee participation on European level which guarantees workers the right to information and consultation. The employees' representatives of all undertakings of transnational company were given the opportunity to voice their opinion about the decisions to be made by central management of the company. In this article three major topics are discussed: the role of European Works Councils in EU countries, the range of these institutions of employee participation on European level and changes in EWCs' functioning introduced by the new EWC directive. The main aim of the paper is to present diverse patterns of these institutions as well as to attempt the evaluation of EWCs effectiveness and their influence on the system of industrial relations in Europe. – – We wrzesńiu 2011 r. mineła 15 rocznica wejsćia w zẏcie pierwszej unijnej dyrektywy powołujacej Europejskie Rady Zakładowe (ERZ). W tym roku takzė zaczeła obowiazywacńowa wersja tej regulacji, tzn. dyrektywa 2009/38/EC. ERZ sa forma reprezentacyjnej partycypacji pracowniczej na poziomie europejskim, ktoŕa gwarantuje pracownikom prawo do informacji i konsultacji. Reprezentanci załogi otrzymali mozl̇iwosćẃyrazȧnia swoich opinii o projektowanych decyzjach centralnego kierownictwa przedsiebiorstwa transnarodowego, ktoŕe odnosza sie do pracownikoẃ we wszystkich zakładach tego przedsiebiorstwa. Niniejszy artykuł koncentruje sie trzech głoẃnych obszarach: roli Europejskich Rad Zakładowych w krajach UE, zasiegu tych instytucji partycypacji na poziomie europejskim i zmianach w funkcjonowaniu ERZ spowodowanych wprowadzeniem nowej dyrektywy. Głoẃnym celem artykułu jest przedstawienie roźṅych rodzajoẃ tych instytucji oraz prob́a oceny efektywnosći ERZ i ich wpływu na system stosunkoẃ przemysłowych w Europie.
Keywords: 330